Karakteristik Ph Dan Suhu Dalam Proses Pembuatan Biogas Dari Substrat Limbah Rumah Makan, Limbah Cair Tahu Dan Kotoran Sapi - Violla Dwivannie; Aryo Sasmita; Etty Pratiwi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Restaurant waste is biomass which has the potential to be developed into renewable energy in the form of biogas. The choice of restaurant waste is the main substrate for biogas production because the waste contains many elements of organic material which have not been widely used, especially for biogas production. Besides of restaurant waste, tofu liquid waste and cow dung are very potential to be used as additional substrates in the biogas formation process. This research aims to study the effect of variations in the composition of organic waste (restaurant waste, tofu wastewater and cow dung) on the quality of methane gas in biogas production. The research was conducted using an 30-liter anaerobic biodigester with a working volume of 22.5 liters. The research variables are substrate variations, namely 100% restaurant waste, 50% restaurant waste : 50% tofu liquid waste, and 93.75% restaurant waste : 6.25% cow dungThe results showed that the initial pH value of the three biodigesters ranged from 6.63 to 6.7 where the pH range was still within the ideal pH value in making biogas, which ranged from 6.6 to 7.6. While the temperature of each reactor in this study has fluctuated, ie 28 ° C - 29.7 ° C, in this temperature range biogas can still be developed. Keywords : Anaerobic process, biogas, restaurant waste, tofu liquid waste, cow dung